Distinct oncogenic Ras signals characterized by profound differences in flux through the RasGDP/RasGTP cycle. (2nd January 2017) - Mues, Marsilius; Roose, Jeroen P.
ABSTRACT: T cell acute lymphoblastic leukemia/lymphoma (T-ALL) is an aggressive bone marrow cancer in children and adults, and chemotherapy often fails for relapsing patients. Molecularly targeted therapy is hindered by heterogeneity in T-ALL and mechanistic details of the affected pathways in T-ALL are needed. Deregulation of Ras signals is common in T-ALL. Ras is genetically mutated to a constitutively active form in about 15% of all haematopoietic malignancies, but there is a range of other ways to augment signaling through the Ras pathway. Several groups including our own uncovered that RasGRP1 overexpression leads to T-ALL in mouse models and in pediatric T-ALL patients, and we reported that this Ras guanine nucleotide exchange factor, RasGRP1, cooperates with cytokines to drive leukemogenesis. In our recent study by Ksionda et al. we analyzed the molecular details of cytokine receptor-RasGRP1-Ras signals in T-ALL and compared these to signals from mutated Ras alleles, which yielded several surprising results. Examples are the striking differences in flux through the RasGDP/RasGTP cycle in distinct T-ALL or unexpected differences in wiring of the Ras signaling pathway between T-ALL and normal developing T cells, which we will discuss here.